Should All Athletes Use Explosive Lifting? A Commentary - Chiu, L. (International Journal of Sports Science and Coaching, 2013)
Newton and Jenkins` article argues for the inclusion of explosive strength training in the preparation of athletes. Moreover, they highlight the importance for coaches to develop their knowledge of explosive strength training to maximize effectiveness in practice. While resistance training in athletic populations has grown in popularity over the last two decades, my observations as a scientist, educator and coach are that the underlying principles of explosive strength training are not well understood. An appreciation of the physiology and biomechanics of explosive strength training is required to appropriately design resistance training programs to enhance performance.